Three-Dimensional Gradient Metamaterial Devices Coupled with Phononic Crystals for Acoustic Enhancement Sensing - Xinsa Zhao; Guodong Hao; Yu Shang; Jianning Han (Crystals, 2023)
Conventional acoustic systems exhibit a difficulty in sensing weak acoustic fault signals in complex mechanical vibration environments. Therefore, it is necessary to develop an acoustic sensing mode and a corresponding functional device with pressure amplification. This paper proposes a three-dimensional device, coupling gradient acoustic metamaterials (GAM) with phononic crystals (GAM–PC). The strong wave compression effect coupled with the phononic crystal equivalent medium mechanism is utilized to achieve the enhancement of weak acoustic signal perception at the target frequency. The superior amplification capability of the GAM–PC structure for the amplitude of loud signals is verified by numerical simulations and experiments. Moreover, the GAM–PC structure has a narrower bandwidth per slit, making it more frequency selective. Furthermore, the structure can separate different frequency components. This work is expected to be applied to signal monitoring in environments with strong noise.